KESIAPAN REMAJA PUTERI DALAM MENGHADAPI 1000 HARI PERTAMA KEHIDUPAN DITINJAU DARI KUALITAS DAN KUANTITAS KONSUMSI PANGAN - Safitri, Amalia (GIZI INDONESIA, 2018)
The optimal quality of human resources is determined bythe time of fetal development starteduntil the age of two years (1000 days of the first life). The successof its development is influenced by several factors;someof them arethe quality and quantity of food, especially for adolescent girls, to reach the normalnutrition status. Girlsneed to pay more attention to their health especially totheir nutritional status before pregnancybecause thismay affect the nutritional status of baby born. The purpose of this studywasto see the readiness of adolescent girls in facing 1000 days of life by looking at the quality and quantity of their food consumption in accordance with balanced nutrition. The data were taken from the Individual Food Consumption Survey(SKMI)taken in 2014, toevaluateat the diversity, proportion and adequacy of consumption amongadolescent girls aged 10-18 years. The result shows that in terms of diversity, it was categorized as“good”(82.5 percent), but forthe proportion was 22.7 percent, andforconsumption sufficiency, indicated good was30.3 percent. When viewed from the food consumption in term of quality and quantity (combined diversity, proportion and adequacy)showed that adolescent girlswho metthe criteria were still very little (6.7 percent). This studyconcludedthat the preparedness of adolescent girls in facing 1000 days of life is still lowespecially theirfood consumption. It is paid to beattention from all partiesthatnutrition improvement during teenager andpregnancy periods is priority.